About Organizing Practical Training of Future Specialists at Scientific and Research Institute of Informational Technologies of Kherson State University (Journal of Information Technologies in Education (ITE), 2008)
In the report the Research Institute of Information Technologies of Kherson State University operational experience is expounded in practical students’ preparation of specialty “Applied mathematics. Computer Science”. From our point of view, this experience will be useful for all institutions of higher education, which train specialists in the area of programming.